Use of Integra Dermal Regeneration Template for Limb Salvage in Diabetic Patients With No-Option Critical Limb Ischemia. (June 2021) - Dalla Paola, Luca; Cimaglia, Paolo; Carone, Anna; Boscarino, Giulio; Scavone, Giuseppe
We have analyzed in a retrospective study of consecutive diabetic patients affected by no-option critical limb ischemia (CLI) the efficacy of the dermal substitute Integra Dermal Regeneration Template for treatment of complicated foot lesions. The primary end point was limb salvage and 1-year amputation-free survival. The secondary end point was healing time of surgical site. Between October 2014 and October 2017, 1024 patients with diabetic foot ulcer (DFU) and CLI were admitted. In 84 patients (8.2%), there was a failure in distal revascularization with a persistent CLI after the procedure. Despite the persistent CLI, a group of 26 patients of this cohort obtained complete wound healing. Among them, 13 patients were treated with surgical debridement or open amputations and application of dermal substitute Integra Dermal Regeneration Template and the other 13 patients were treated without any dermal substitute. The Integra group healed within a mean time of 83.5 days, and the control group healed within a mean of 139 days ( P = .028). No major amputation was carried out at 1-year follow-up in the Integra group versus 15% in the control group. A conservative foot surgery or an approach with minor amputation in diabetic patients with no-option CLI may achieve limb salvage. The use of Integra Dermal Regeneration Template in patients with DFU and no-option CLI may be a useful option in a limb salvage program.